Juridical Interpretation of Non-Fully Executable Judgments in The Administrative Court - Kusman; Hambali; Utama, Yos Johan; Alw, Lita Tyesta (Pusat Strategi Kebijakan Hukum dan Peradilan Mahkamah Agung RI, 2025)
Judgments that cannot be fully executed are frequently encountered in civil service disputes. Rehabilitation obligations are often hindered by changes in circumstances, which have consequently given rise to the notion of compensation. Determining compensation amounts also faces challenges, particularly due to tensions between legal norms and practical realities. This study pursues two main objectives: first, to examine the criteria that characterize judgments that cannot be fully executed, and second, to describe the implementation of compensation as a substitute mechanism in such cases. The research adopts a normative legal methodology utilizing statutory and conceptual approaches. The findings lead to two primary conclusions: first, judgments that cannot be fully executed are identified in cases where rehabilitation obligations in civil service disputes face specific obstacles, including (1) the plaintiff’s legal status no longer qualifying them to return to their former position; (2) the plaintiff’s position having been filled by another person; and (3) changes in the organizational structure. Second, the implementation of compensation is based on actual losses suffered by the plaintiff resulting from a State Administrative Decision that was declared invalid by the court. The amount of compensation is determined through an agreement between the plaintiff and the defendant. If such an agreement cannot be reached, the chief judge of the administrative court is authorized to determine a fair amount of compensation in accordance with the principles of propriety and reasonableness. The study highlights the need for procedural reform to address the gap between legal provisions and their practical application in executing administrative court judgments.